Current trends and future prospects of N-acetylcysteine utilizations in Parkinson's disease: A literature network analysis - Muthmainah Muthmainah, PhD; Nanang Wiyono, MD; Faris K. Syah, MD; Adityas Purnianto, PhD; Ratih D. Yudhani, MD; Brian Wasita, PhD (Journal of Taibah University Medical Sciences, 2025)
الملخص: مرض باركنسون هو اضطراب عصبي تنكسي شائع ليس له علاج شاف. يلعب الإجهاد التأكسدي دورا هاما في تطور المرض، مما أثار الاهتمام بـمركب ن-أسيتيل-سيستين، وهو مضاد أكسدة قوي ومادة أولية للسيستين، كعامل علاجي محتمل. قمنا بتحليل 4٢١ مقالة منشورة في قاعدة بيانات سكوبس لتقييم التوجه الحالي والإمكانات المستقبلية للبحوث المتعلقة باستخدام ن-أسيتيل-سيستين في مرض باركنسون. بلغ عدد المنشورات المتعلقة بهذا الموضوع ذروته في عام ٢٠١٠، ثم انخفض تدريجيا بعد ذلك. حددنا أربع مجموعات بحثية رئيسية تتعلق بالآلية المحتملة لتأثيرات ن-أسيتيل-سيستين على تطور مرض باركنسون. وتشمل هذه الأبحاث التي تركز على تأثيرات ن-أسيتيل-سيستين على الإجهاد التأكسدي، وخلل الميتوكوندريا، وتراكم البروتينات غير الطبيعي، وتصفية البروتينات، والالتهاب. ويُعد البحث في تأثير ن-أسيتيل-سيستين على مرض باركنسون لدى البشر مجالا بحثيا محتملا. Abstract: Parkinson's disease (PD) is a prevalent neurodegenerative disorder without a definitive cure. Oxidative stress is significantly implicated in its pathogenesis, prompting interest in N-acetylcysteine (NAC), a strong antioxidant and cysteine precursor, as a potential therapeutic agent. We conducted a bibliometric analysis of 421 Scopus articles to assess current trend and future potential of research on the use of NAC in Parkinson's disease. The number of publications related to this topic reached the peaked in 2010 and gradually decreased afterward. We identified 4 main clusters of research theme related to the potential mechanism of NAC effects on Parkinson's disease progression. These include research focusing on NAC effects on oxidative stress, dysfunction of the mitochondria, aberrant protein accumulation and clearance and inflammation. Investigating NAC effect for Parkinson's disease in human is a potential research area.